T cell regulation in adult transplantation tolerance. - Davies, J; Martin, G; Phillips, J; Marshall, SE; Cobbold, S; Waldmann, H (1996)
An encounter of the mature immune system with Ag usually leads to an immune response. If Ag is administered with CD4- and CD8-specific mAbs, the outcome of the response can be tolerance. This form of tolerance is peripheral, Ag specific, and maintained lifelong, and is associated with the suppression of nontolerant cells by CD4 cells of the tolerant host. Here we demonstrate that the degree of suppression is dependent on the number of suppressor cells. A neutralizing anti-IL-4 Ab was partially able to inhibit suppression, indicating a role for IL-4 in the regulation of Th1 rejection responses.